Research on the current motivation mechanism of Chinese civil servants - Sun, Yijia (2017)
Motivation focuses on the future, and provides direction, intensity, and continuity for the behaviour of organisational members, thus playing a significant role in human resource management. Moreover, the efficiency and performance of civil servants directly affect the quality of government public services. Particularly in the current anti-corruption environment, the behaviours of civil servants are under the strict supervision, and the welfare and privileges are increasingly standardised, which inevitably affect their work motivation and satisfaction. Therefore, it is necessary to improve the current civil servant motivation mechanism to facilitate work engagement of employees and the administration efficiency of the government. In this case, this dissertation mainly investigates the current situation of Chinese public servants’ motivation mechanism through questionnaires, analyses the drawbacks of various motivators, and proposes corresponding suggestions for the improvement of public servants motivation system in the new period.